HISTORIS, DAYA TARIK WISATA DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN BERKUNJUNG DI DE TJOLOMADOE - Nova Susanti; Ida Aryati; Ratna Damayanti (Faculty of Economic and Business, University of Pasundan, 2019)
The purpose of this research is to analyze the effect of either simultaneously or partial historical, tourist attraction and electronic word of mouth to decision visit in De Tjolomadoe Karanganyar, Central Java. The research uses descriptive quantitative. The population is visitors at De Tjolomadoe Karanganyar, Central Java. The sample is 100 respondents. Sampling technique uses accidental sampling. The technique used to analyze the data is multiple linier regression. The results of F-test shows that historical, tourist attraction and electronic word of mouth (e-WOM) have simultaneous and significant influence to decision visit. The results of t-test showed that historical, tourist attraction, electronic word of mouth have positive and significant influence to decision visit in De Tjolomadoe Karanganyar Central Java